Literature Review: Pentingnya Memahami Gaya Belajar Anak dalam Pembelajaran di Kelas pada Perspektif Teori dan Psikologi Belajar Anak Sekolah Dasar - Dhaifina Rasyiqa; Rahma Moutia Asmini; Nyayu Sofiah; Dewi Sartika; Uswatun Hasanah; Indi Arisandi; Monica Ika Saputri; Rizki Jamali; Intan Nur Azizah; Sri Lestari; Liza Murniviyanty; Syska Purnama Sari; Arizona Arizona (Journal of Society Counseling, 2026)
Basic education has an important role in developing the potential of students, especially through an effective learning process that is in accordance with student characteristics. One of the factors that affects the success of learning is learning style, which is the way an individual receives, processes, and understands information. This study aims to examine the importance of understanding students' learning styles from the perspective of learning theory and psychology in elementary schools. The method used is qualitative descriptive through literature studies by examining various sources such as books, scientific journals, and related articles. The results of the study show that learning styles are divided into three main types, namely visual, auditory, and kinesthetic, each of which has different characteristics in the learning process. In addition, learning theories such as behaviorism, cognitivism, constructivism, and humanistic provide a foundation for understanding how students learn optimally. Understanding learning styles allows teachers to design learning strategies, methods, and media that are more varied, interesting, and in accordance with students' needs. Thus, learning becomes more effective, increases motivation, and improves student learning outcomes. Therefore, teachers need to recognize and accommodate differences in students' learning styles to create an optimal and meaningful learning process in elementary school.